Cancer-associated fibroblasts in hepatocellular carcinoma: origins, heterogeneity, and therapeutic implications - Shi, Xin; Zhu, Weixiong; Zhang, Jianpeng; Fan, Chuanlei; Zhang, Jing (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) is a globally prevalent malignancy. This disease often progresses rapidly, resulting in many patients being diagnosed at a late stage, making early detection and intervention a major clinical challenge. Postoperative recurrence and metastasis rates remain significantly high, and no effective prevention strategies are currently available. Cancer-associated fibroblasts (CAFs) are essential components in the reorganization of the tumor microenvironment (TME), as they can modulate cancer cell proliferation, migration, invasion, and chemoresistance through diverse mechanisms or signaling pathways, including the release of cytokines, remodeling of the extracellular matrix, and the evasion of the immune response. This review offers a detailed overview of the cellular origins, subtype diversity, and functional differences among CAFs. In addition, it depicts the expression profiles of key markers in various CAF subtypes and clarifies essential signaling pathways and mechanisms of CAFs. Additionally, we discuss current and future therapeutic strategies targeting CAFs in the context of HCC. This review provides critical insights into future studies on novel therapeutic approaches for CAFs.